Traditional Celebrations in Chile: A Cultural Heritage in Crisis?; [Fiestas Costumbristas en Chile: ¿Un Patrimonio Cultural en Crisis?] - Lacoste, P (Universidad Nacional de La Plata, 2025)
The impact of massification on the festivities associated with national holidays in the Metropolitan, Los Ríos and Aysén regions is analyzed. The comparison allows us to interpret the role of regional identities in heritage management. An ethnographic observation work was carried out of the living museum (sale of crafts), the typical food court, and the artistic proposal (music, dance, theater). In mass festivals there is a devaluation of local crafts and gastronomy, which is repeated in the artistic field: mass music popular operates to the detriment of regional artists and music. This loss is directly proportional to the size of the recreational market associated with the festivals and to the identity roots, finding that regional celebrations present advantages in the protection of heritage. Lines of action are suggested aimed at better safeguarding the regional cultural wealth. © 2025 Universidad Nacional de La Plata. All rights reserved.